2021
DOI: 10.1111/are.15218
|View full text |Cite
|
Sign up to set email alerts
|

Effect of anthocyanin extract from Roselle,Hibiscus sabdariffa, calyx on haematological, biochemical and immunological parameters of rainbow trout,Oncorhynchus mykiss

Abstract: Aquaculture has an important role in global protein supply all over the world, and rainbow trout, Oncorhynchus mykiss, is one of the most important coldwater fish species in aquaculture industry. Rainbow trout global production exceeded 800,000 tons in 2017, which more than 20% of this value has been related to Iran (FAO, 2019). Due to its importance, extended researches have been conducted on nutritional aspects of this species. Nutrition is an important factor in aquaculture, because it directly affects fish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 56 publications
2
9
0
Order By: Relevance
“…The studies in peer-reviewed journals revealed that HG fish fed with various additives had a higher number of RBC. For example, ellagic acid in rainbow trout ( Oncorhynchus mykiss ) [ 57 ], brewer’s yeast in Nile tilapia [ 31 ], a combination of herbs in common carp ( Cyprinus carpio ) [ 58 ], butyric acid glycerides in yellowfin seabream ( Acanthopagrus latus ) [ 59 ], roselle anthocyanin extract in rainbow trout [ 60 ] and chitosan nanoparticles in Nile tilapia [ 43 ] increased the number of RBCs. Increased growth in these treatments demonstrates that fish benefit from optimised oxygen delivery, and there may be a direct relationship between growth and RBC numbers.…”
Section: Red Blood Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies in peer-reviewed journals revealed that HG fish fed with various additives had a higher number of RBC. For example, ellagic acid in rainbow trout ( Oncorhynchus mykiss ) [ 57 ], brewer’s yeast in Nile tilapia [ 31 ], a combination of herbs in common carp ( Cyprinus carpio ) [ 58 ], butyric acid glycerides in yellowfin seabream ( Acanthopagrus latus ) [ 59 ], roselle anthocyanin extract in rainbow trout [ 60 ] and chitosan nanoparticles in Nile tilapia [ 43 ] increased the number of RBCs. Increased growth in these treatments demonstrates that fish benefit from optimised oxygen delivery, and there may be a direct relationship between growth and RBC numbers.…”
Section: Red Blood Cellsmentioning
confidence: 99%
“…The higher number of WBC in HG fish fed on barberry root [ 24 ], garlic [ 25 ], ellagic acid [ 57 ], zeolite [ 69 ], butyric acid glycerides [ 59 ], prebiotic inulin [ 48 ] and selenium nanoparticulate [ 70 ] were observed. Conversely, no relation between growth and WBC was observed in different fish species when they were fed on roselle anthocyanin extract [ 60 ], exopolysaccharide [ 27 ] and coriander extract [ 61 ]. The growth and WBC trends in FM/FO studies were similar ( Table S3 ).…”
Section: White Blood Cellsmentioning
confidence: 99%
“…Previous studies showed that besides microalgae, other plant sources can be a good source of carotenoids for aquaculture animals (Supamattaya et al, 2005;Jomeh et al,2021). Roselle, Hibiscus sabdariffa, is a flowering plant that grows in tropical and subtropical countries.…”
mentioning
confidence: 99%
“…However, the usage of roselle was not limited to human consumption. Previously, roselle meal or extract has been tested in aquatic animals and showed improving the growth, hematological profile, antioxidant characteristics, and immunological parameters of the animals (Pérez-Escalante et al, 2012;Hoseini et al, 2021, Jomeh et al, 2021. In most practices, the roselle was discarded after the extraction.…”
mentioning
confidence: 99%
See 1 more Smart Citation